Signalling, trafficking and glucoregulatory properties of glucagon-like peptide-1 receptor agonists exendin-4 and lixisenatide. - Pickford,P; Lucey,M; Fang,Z; Bitsi,S; Bernardino,de la Serna J; Broichhagen,J; Hodson,DJ; Minnion,J; Rutter,GA; Bloom,SR; Tomas,A; Jones,B (British Journal of Pharmacology, 2020)
BACKGROUND AND PURPOSE: Amino acid substitutions at the N-termini of glucagon-like peptide-1 receptor agonist (GLP-1RA) peptides result in distinct patterns of intracellular signalling, sub-cellular trafficking and efficacy in vivo. Here we aimed to determine whether sequence differences at the ligand C-termini of clinically approved GLP-1RAs exendin-4 and lixisenatide lead to similar phenomena. EXPERIMENTAL APPROACH: Exendin-4, lixisenatide, and N-terminally substituted analogues with biased signalling characteristics were compared across a range of in vitro trafficking and signalling assays in different cell types. Fluorescent ligands and new time-resolved FRET approaches were developed to study agonist behaviours at the cellular and sub-cellular level. Anti-hyperglycaemic and anorectic effects of each parent ligand, and their biased derivatives, were assessed in mice. KEY RESULTS: Lixisenatide and exendin-4 showed equal binding affinity, but lixisenatide was 5-fold less potent for cAMP signalling. Both peptides induced extensive GLP-1R clustering in the plasma membrane and were rapidly endocytosed, but the GLP-1R recycled more slowly to the cell surface after lixisenatide treatment. These combined deficits resulted in reduced maximal sustained insulin secretion and reduced anti-hyperglycaemic and anorectic effects in mice with lixisenatide. N-terminal substitution of His1 by Phe1 to both ligands had favourable effects on their pharmacology, resulting in improved insulin release and lowering of blood glucose. CONCLUSION AND IMPLICATIONS: Changes to the C-terminus of exendin-4 affect signalling potency and GLP-1R trafficking via mechanisms unrelated to GLP-1R occupancy. These differences were associated with changes in their ability to control blood glucose and therefore may be therapeutically relevant.